The Evolving Role of Medical Assistants in Healthcare: A Systematic Review of Their Impact on Patient Care and Clinical Efficiency (Cuestiones de Fisioterapia, 2025)
The role of medical assistants (MAs) in healthcare has evolved significantly, contributing to both patient careand clinical efficiency. This systematic review examines the impact of MAs on healthcare delivery, focusing ontheir role in enhancing patient outcomes, optimizing clinical workflows, and alleviating the administrativeburden on healthcare professionals. A comprehensive literature search was conducted across majordatabases, selecting studies published from 2016 onwards that explore the contributions of MAs in varioushealthcare settings. Findings indicate that MAs play a crucial role in patient education, care coordination, andprocedural support, leading to improved patient satisfaction and adherence to treatment plans. Additionally,their involvement in administrative and clinical tasks enhances workflow efficiency, allowing physicians andnurses to focus on more complex medical procedures. Despite their growing significance, challenges such asrole ambiguity, training disparities, and regulatory limitations persist. This review underscores the need forstandardized training programs, expanded scopes of practice, and further research to evaluate the long-termbenefits of MAs in healthcare systems.